Вы находитесь на странице: 1из 6

F4 Online Test 1 Solution

1. The answer is B.

x2 + 6 x − 1 = 0
( x + 6 x + 9) − 1 − 9 = 0
( x + 3) 2 − 10 = 0

2. The answer is A.
y = 2 x2 − 8x + 1
= 2( x 2 − 4 x) + 1
4
= 2( x 2 − 4 x + ( )2 ) + 1 − 2(4)
2
2
= 2( x − 2) − 7
∴ The vertex is (2,-7)

3. The answer is D.
2 x 2 + 3x + k = 1
2 x 2 + 3x + k − 1 = 0
∵ The equation has real roots, so ∆ ≥ 0
∆ = 32 − 4(2)(k − 1) ≥ 0
9 − 8(k − 1) ≥ 0
9
(k − 1) ≤
8
17
k≤
8

4. The answer is B.

4 x 2 + kx + 1 = 0
∵ The equation has equal real roots, so ∆ = 0
∆ = k 2 − 4(4)(1) = 0
k 2 = 16
k = ±4
5. The answer is B.
h = −3t 2 + 15t > 12
3t 2 − 15t + 12 < 0
t 2 − 5t + 4 < 0
(t − 1)(t − 4) < 0
1< t < 4
The duration of time = 4 − 1 = 3 seconds

6. The answer is C.
( x + 3)2 = 4( x + 3)
( x + 3)2 − 4( x + 3) = 0
( x + 3)( x + 3 − 4) = 0
( x + 3)( x − 1) = 0
x = 1 or -3

7. The answer is A.

(5 x − 1)2 − 3(5 x − 1) − 4 = 0
Let y = 5 x − 1
y2 − 3 y − 4 = 0
( y − 4)( y + 1) = 0
y = −1 or 4
5 x − 1 = −1 or 5 x − 1 = 4
5 x = 0 (Rej.) or 5
∴x =1
8. The answer is C.
2 x + 5 x − 12 = 0
Let y = x
2 y 2 + 5 y − 12 = 0
(2 y − 3)( y + 4) = 0
3
y = or − 4
2
3
x = or − 4
2
9
x = or 16
4
9 9 9 9 15
When x = , 2( ) + 5 ( ) − 12 = + − 12 = 0
4 4 4 2 2
When x = 16, 2(16) + 5 16 − 12 = 32 + 20 − 12 = 40 ≠ 0
9
∴x =
4

9. The answer is B.

8 35
3− − =0
x x2
1
Let y =
x
3 − 8 y − 35 y 2 = 0
35 y 2 + 8 y − 3 = 0
(7 y + 3)(5 y − 1) = 0
3 1
y = − or
7 5
1 3 1
= − or
x 7 5
7
x = − or 5
3
10. The answer is B.
2 x 12
+ = 2
x−3 x +3 x −9
2( x + 3) + x( x − 3) = 12
2 x + 6 + x 2 − 3 x = 12
x2 − x − 6 = 0
x = −2 or x = 3 (rejected ∵ x ≠ 3)

11. The answer is A.

f ( x) = − x 2 + x
f (2 x − 1) = −(2 x − 1) 2 + (2 x − 1)
= −(4 x 2 − 4 x + 1) + (2 x − 1)
= −4 x 2 + 4 x − 1 + 2 x − 1
= −4 x 2 + 6 x − 2

12. The answer is C.


f ( x) = x 2 + 2 x + 2
f ( x + 1) − f ( x) = [( x + 1) 2 + 2( x + 1) + 2] − [ x 2 + 2 x + 2]
= [ x 2 + 2 x + 1 + 2 x + 2 + 2] − [ x 2 + 2 x + 2]
= 2x + 3

13. The answer is C.


1
 x + 2 y − 2 = 0----------------(1)

 2 + y − 7 = 0------------------(2)
 x
1
From (1), = 2 − 2 y ---------(3)
x
Put (3) into (2),
2(2 − 2 y ) + y − 7 = 0
4 − 4y + y − 7 = 0
3 y = −3
y = −1----------------------------(4)
Put (4) into (3),
1
= 2 − 2(−1) = 4
x
1
x=
4
14. The answer is C.
The curve is open upwards.
∴a > 0
Since the curve is on the right side and a > 0,
∴b < 0
The y-intercept is < 0
∴−c < 0 ⇒ c > 0
I and III is true.

15. The answer is A.


10 = 62 − a (6) + 22
6a = 48
a =8

16. The answer is B.


From question 14, y = t 2 − 8t + 22
8 8
y = (t 2 − 8t + ( ) 2 ) + 22 − ( )2
2 2
2
y = (t − 4) + 6
∴ y will be the minimum when t = 4

17. The answer is B.


From question 14, y = t 2 − 8t + 22
8 8
y = (t 2 − 8t + ( ) 2 ) + 22 − ( )2
2 2
2
y = (t − 4) + 6
∴ y will be the minimum when t = 4
When t = 4, y = (4 − 4) 2 + 6 = 6

18. The answer is D.


f ( x) = ax + b
f (3) = 3a + b = 12..................(i )
f (4) = 4a + b = 17..................(ii )
by solving (i )(ii )
a = 5, b = −3
19. The answer is C.

f (3b) = 27b3 − 27b 2


=(3b)3 − 3(3b) 2
f (2a ) = (2a )3 − 3(2a) 2
= 8a 3 − 12a 2
20. The answer is C.

f ( x) = x 2 − 2 x − 3
f (−1) = (−1) 2 − 2(−1) − 3 = 1 + 2 − 3 = 0
f [ f (−1)] = f (0)
f (0) = −3